SALES FORECASTING MODELS AS A BASIS FOR BUDGET PREPARATION IN THE LOCAL CREATIVE INDUSTRY: A CASE STUDY OF HIKMAH SASIRANGAN MSME - Hikmahwati; M. Rizki Maulana; Julkawait (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This study aims to develop a sales forecasting model as a basis for budget preparation in the local creative industry, with a case study of Hikmah Sasirangan MSME in South Kalimantan. The object of the study focuses on two main products, namely satin fabric and silk fabric, using historical sales data from 2020 to 2024. This research employs a descriptive qualitative approach combined with quantitative sales forecasting analysis to understand how forecasting results are interpreted and utilized in managerial decision-making. Data were collected through interviews, observation, and documentation, including sales records and production data. Two forecasting methods were applied, namely the Weighted Moving Average (WMA) and the Semi Average method. The results indicate that the Semi Average method produces higher sales estimates as it captures long-term linear trends, while the WMA method yields more conservative forecasts by emphasizing recent sales data. Based on the comparison, the WMA method was selected as the basis for preparing the 2025 sales budget, as it is considered more realistic and aligned with the production capacity and demand characteristics of the MSME. The findings suggest that selecting an appropriate forecasting model is crucial for improving budgeting accuracy and supporting prudent financial planning in local creative MSMEs.